Instytucja prawyborów w Polsce. Prawybory prezydenckie (1995–2005) - Adamczyk, Anita (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2011)
This paper is devoted to the presidential pre-elections in Poland. It is the second part of a study concerning the parliamentary pre-elections held in Poland. The timeframe of this pa- per covers the period between 1995 and 2005. The paper begins with an overall analysis of pre-elections organized by political parties in Poland, following American patterns, where a candidate for the presidency is to represent a certain group. Next, the pre-elections held in the town of Wrzeœnia in 1995 and 2005, in Nysa in 2000 and Szczecin in 2005 are explored. An assessment of the accuracy of these pre-elections’ results is carried out. The paper also discusses other initiatives similar to pre-elections, addressed at young peo- ple in high schools and universities.
The institution of pre-elections in Poland. Presidential pre-elections (1995–2005)
Keywords: prawybory prezydenckie w Polsce